The photographs of Zygmunt Bauman - Beilharz, Peter; Wolff, Janet (Manchester University Press, 2023)
Zygmunt Bauman, internationally known and revered as the sociologist of postmodernity and of 'liquid' society, was for about a decade a serious and dedicated photographer. This book presents his black-and-white photographs from the 1980s, together with a range of essays, by colleagues, friends and family, about his work with images. The importance of his wife, Janina Bauman, in his life and work is acknowledged, with essays on photographs he took of her and also on her work in the film industry in Poland.